Manajemen Syariah Sebagai Dasar Pengelolaan Bank Syariah - Nadia Rakhil Azizah; Ngizatul Milah Khoirun Nisa; Cevira Putri Nabila; Hilda Nor Fani; Binti Nur Asiyah (Kajian Ekonomi dan Akuntansi Terapan, 2024)
Sharia management as the basis for the management of Islamic banks in Indonesia. Sharia management is an approach that integrates Islamic values in decision-making and operational implementation, emphasizing the principles of ethics, fairness, and transparency. The article examines the definition of sharia management, the basics of sharia bank management sourced from the Qur'an and Hadith, as well as the implementation of sharia management principles in management functions such as organizing, actuating, controlling, and evaluating. The goal is to provide a more comprehensive understanding of sharia management in the context of sharia banking, as well as to encourage the improvement of the quality of sharia bank management in Indonesia so that it can play a more optimal role in encouraging sustainable and equitable economic growth.